OVINE PARATUBERCULOSIS-A HISTOPATHOLOGICAL STUDY FROM PAKISTAN - A. Sikandar; A. H. Cheema; M. Adil; M. Younus; H. Zaneb; M. A. Zaman M. Y. Tipu; S. Masood (Journal of Animal and Plant Sciences, 2013)
This study was conducted to elucidate the histopathological depiction of ovine paratuberculosis. Tissue samples were randomly collected from 47 sheep slaughtered at two municipal abattoirs of district Jhang, Pakistan. The tissue samples were inspected for the presence of Mycobacterium avium subspecies paratuberculosis (MAP) by means of acid-fast staining and gross/histopathological examination. Indirect ELISA was also performed for the confirmation of paratuberculosis. Intestinal pathological lesions were observed in 04.12% animals. While only 03.77% of mesenteric lymph nodes (MLN) were associated with gross lesions. Acid-fast staining of tissue hard pressed smears were positive for MAP in 12.76% intestinal and 10.63% MLN tissue samples. Similarly Ziehl-Neelsen (ZN) staining of the histopathological tissue sections of MAP positive smear samples reflected the occurrence of acid-fast bacilli in 100%intestinal as well as lymph nodes samples. This indicated the superiority of intestinal samples over mesenteric lymph nodes and hence tissue section could be considered to be a comparatively better preparation for the analysis of paratuberculosis with ZN staining technique. ELISA confirmed 10.63% samples positive for MAP. It was concluded from the study that infection of MAP could be precisely identified by histopathology and indirect ELISA, which tends to be unlikely if merely based upon acid-fast staining and gross examination.
Keywords: Sheep; Paratuberculosis; Histopathology; ELISA